IL-6 Impairs Vaccine Responses in Neonatal Mice - Yang, Jiyeon; Sakai, Jiro; Siddiqui, Shafiuddin; Lee, Robert C.; Ireland, Derek D. C.; Verthelyi, Daniela; Akkoyunlu, Mustafa (Frontiers in Immunology, 2018)
The inability of infants to mount proper follicular helper T (TFH) cell response renders this age group susceptible to infectious diseases. Initial instruction of T cells by antigen presenting cells and subsequent differentiation into TFH cells are controlled by T cell receptor signal strength, co-stimulatory molecules and cytokines such as IL-6 and IL-21. In immunized adults, IL-6 promotes TFH development by increasing the expression of CXCR5 and the TFH master transcription factor, B cell lymphoma 6. Underscoring the importance of IL-6 in TFH generation, we found improved antibody responses accompanied by increased TFH cells and decreased follicular regulatory helper T (TFR) cells, a Foxp3 expressing inhibitory CD4+ T cell occupying the germinal center (GC), when a tetanus toxoid conjugated pneumococcal polysaccharide type 14 vaccine was injected in adult mice together with IL-6. Paradoxically, in neonates IL-6 containing PPS14-TT vaccine suppressed the already impaired TFH development and antibody responses in addition to increasing TFR cell population. Supporting the diminished TFH development, we detected lower frequency of phospho-STAT-3+ TFH in immunized neonatal T cells after IL-6 stimulation than adult cells. Moreover, IL-6 induced more phospho-STAT-3+ TFR in neonatal cells than adult cells. We also measured lower expression of IL-6R on TFH cells and higher expression on TFR cells in neonatal cells than adult cells, a possible explanation for the difference in IL-6 induced signaling in different age groups. Supporting the flow cytometry findings, microscopic examination revealed the localization of Treg cells in the splenic interfollicular niches of immunized adult mice compared to splenic follicles in neonatal mice. In addition to the limitations in the formation of IL-21 producing Tfh cells, neonatal mice GC B cells also expressed lower levels of IL-21R in comparison to the adult mice cells. These findings point to diminished IL-6 activity on neonatal TFH cells as an underlying mechanism of the increased TFR : TFH ratio in immunized neonatal mice.